A cross‐sectional study of haemolytic disease of the newborn in Uganda. Issue 12 (7th November 2022) - Dhabangi, Aggrey; Nankunda, Jolly; Okaba, Violet; Nakubulwa, Sarah; Hume, Heather A.; Dzik, Walter H.; Heddle, Nancy M.
Abstract: Background and Objectives: Haemolytic disease of the newborn (HDN) is an immune haemolytic anaemia from maternal alloantibodies. Rh immunoglobulin (RhIg) prophylaxis can prevent alloimmunization to the D antigen. However, RhIg is not universally available in Uganda. ABO incompatibility also causes HDN. We determined the prevalence of HDN among newborn infants with jaundice in Uganda. Materials and Methods: We conducted a prospective cross‐sectional study at Kawempe National Referral Hospital, Kampala, Uganda. Infants aged 0–14 days with neonatal jaundice (or total bilirubin >50 μmol/L) were enrolled. Clinical evaluation and laboratory testing, including ABO, RhD typing and maternal antibody screen, were performed. Results: A total of 466 babies were enrolled. The mean (SD) age was 3.4 (1.5) days. Of newborn babies with jaundice, 17.2% (80/466) had HDN. Babies with HDN had lower haemoglobin (SD); 15.7 (2.7) compared with those without HDN; 16.4 (2.4) g/dL, p  = 0.016; and a higher bilirubin (interquartile range); 241 (200–318) compared with those without HDN; 219 (191–263) μmol/L, p  < 0.001. One baby had anti‐D HDN, while 46/466 had HDN from an ABO incompatibility (anti‐A 43.5% and anti‐B 56.5%); 82% of babies with HDN also had suspected neonatal sepsis or birth asphyxia. About 79.2% (57/72) of mothers did not have ABO/Rh blood group performed antenatally. All infants with HDN survived except one. Conclusion: Among newborn infants with jaundice, HDN is not rare. The majority is due to ABO HDN affecting group A and group B babies equally. Ensuring routine ABO/Rh grouping for all pregnant women is an area for improvement.